Crop Rotation Tool: uma ferramenta para simulação de sequência de cultivos no DSSAT - Cunha, Alex Sebben da (2019)
The prediction of risks and benefits arising from management practices imposed on the agricultural system, especially those aimed at crop sequences and which also result in the prediction of grain yields, has been a constant demand in the agribusiness sector. The application of simulation models in a crop sequence system is an effort to assist in the understanding of the phenomena involved in this production system, with a systemic view. The practical utility of crop simulation models occurs with their integration into decision-making support systems in agriculture, such as DSSAT (Decision Support System for Agrotechnology Transfer), which can account for the availability of water and nitrogen in the soil between one crop and another, for crop sequence simulation. This system enables simulation, but its use is difficult even for experienced users, since the tools developed are not user-friendly and are only available for Windows environments. The objective of this work was the development of a multiplatform tool for crop sequence simulation in DSSAT: the CropRotation Tool. Web technologies such as HTML, CSS and JavaScript were used to develop the proposed tool, and the Electron framework was used to generate the installers for Windows, Linux and MacOS. To integrate the user interface with DSSAT, the jDSSAT JavaScript module was used and expanded to allow reading, writing and processing of DSSAT files related to crop sequences. The developed tool allows the user to list, create, edit and configure crop sequence experiments in a user-friendly manner, using drag and drop features, as well as to run crop sequence simulations and view the results through interactive graphs, allowing the comparison of simulated results with observed results, all in the same interface. To validate the developed tool, a real crop sequence experiment was simulated, involving three harvests of wheat and soybean crops, which took place from June 2015 to June 2018, on a property in southern Brazil, where data on soil, climate, growth and development of the crops were collected. Through data collection and the use of the Crop Rotation Tool 1.2.5 and DSSAT 4.7.5, it was possible to configure and simulate the crop sequence experiment and compare the simulated results with the observed ones.